Development as an Intellectual Process - Sehlare Makgetlaneng (African Journal of Political Science)
This chapter contributes to rethinking African politics by viewing the continent’s development as an intellectual process in which resources are created for the overall satisfaction of human needs. Central to this process is the importance of developing resources over their distribution or consumption volume. Therefore, development as an intellectual process in which society’s resources are created to ensure a better life for its citizens is a central task. The best, most effective, and progressive way to do justice to this task is to put the people at the centre of development in advocacy, debate, and policy. The dominant and yet incorrect view that Africa’s economic sectors such as mining and agriculture are drivers of its economy and development should be replaced with the indispensable role of its human capital under the leadership of intellectuals in its economy and development. This role should be recognised in theory and practice. The point is that economic sectors derive their importance to economy and development from human beings using the knowledge, skills, and determination in deploying their resources to achieve tactical and strategic objectives. Therefore, African intellectuals, creators of leaders and institutions and organisations, producers and disseminators of knowledge and forces dominating the possession and utilisation of human capital without whose organic input no organisation or social pressure can achieve and sustain its strategic objectives, are indispensable to a rethinking of African politics of development they must lead. Their weapons in this role are their leadership of and role in institutions and organisations and individual knowledge and talents as proud continental assets through the mediation of parties under their leadership in deploying Africa’s natural resources, mainly mineral and agricultural resources, inputting the continent and its people first in terms of development.